2023
DOI: 10.3390/md21030182
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Apoptotic Activity of Bioactive Compounds from Seaweeds: Promising Sources for Developing Novel Anticancer Drugs

Abstract: The process by which cancer cells evade or inhibit apoptosis is considered one of the characteristics of cancer. The ability of cancer cells to escape apoptosis contributes to tumor proliferation and promotes metastasis. The discovery of new antitumor agents is essential for cancer treatment due to the lack of selectivity of drugs and cellular resistance to anticancer agents. Several studies showed that macroalgae produce various metabolites with different biological activities among marine organisms. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…IC50 is a crucial indicator for assessing tumor response to therapy; a smaller IC50 value indicates higher sensitivity of tumor cells to this chemotherapeutic agent. IC50 values have been used by many researchers to predict drug sensitivity in order to explore personalized drug therapy guidance for different patients [ 59 , 60 , 61 , 62 , 63 , 64 ]. At the same time, high-risk patients in this study were found to have a greater sensitivity to MP479, SB52334, and other drugs, whereas low-risk patients were found to be more sensitive to JNK inhibitor VIII and TGX221.…”
Section: Discussionmentioning
confidence: 99%
“…IC50 is a crucial indicator for assessing tumor response to therapy; a smaller IC50 value indicates higher sensitivity of tumor cells to this chemotherapeutic agent. IC50 values have been used by many researchers to predict drug sensitivity in order to explore personalized drug therapy guidance for different patients [ 59 , 60 , 61 , 62 , 63 , 64 ]. At the same time, high-risk patients in this study were found to have a greater sensitivity to MP479, SB52334, and other drugs, whereas low-risk patients were found to be more sensitive to JNK inhibitor VIII and TGX221.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research with selenium compounds showed decreased migration and invasion of cancer cells. MRK-107 caused permanent damage, leading to inefficient proliferation recovery, as evaluated using standards that disregard <50% cell growth; these findings demonstrate that MRK-107 also prevents new clone formation in the long term [ 44 , 45 ]. The proliferation index of cancer cells was 2.4–3, demonstrating concentration-dependent cellular quiescence [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to red seaweed, other seaweed species have also been found to possess anti-apoptotic effects. For example, fucoidan, a sulfated polysaccharide found in brown seaweed, has been shown to protect against apoptosis-induced liver injury and promote the survival of liver cells [136].…”
Section: Anti-apoptotic Effectsmentioning
confidence: 99%